2019
DOI: 10.3390/app9163428
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT Analysis for Predicting the Behavior of Part-Solid Nodules with Solid Components Less than 6 mm: Size, Density and Shape Descriptors

Abstract: Persistent part-solid nodules (PSNs) with a solid component <6 mm usually represent minimally invasive adenocarcinomas and are significantly less aggressive than PSNs with a solid component ≥6 mm. However, not all PSNs with a small solid component behave in the same way: some nodules exhibit an indolent course, whereas others exhibit more aggressive behavior. Thus, predicting the future behavior of this subtype of PSN remains a complex and fascinating diagnostic challenge. The main purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 44 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…In their quantitative analysis, the authors defined growth as an increase by more than 11.3% (i.e., more than the coefficient of repeatability of intraobserver variability) of the linear mass density (LMD), a viable two-dimensional alternative to the mass. Moreover, to determine the nodule growth rate, the authors also calculated the LMD-DT by matching the baseline with the last available follow-up CT. Based on the results obtained in their study, Borghesi et al [29] found that both dimensional (area, perimeter, diameter, LMD) and shape features (circularity and solidity) were significantly related to nodule growth, and the strongest association was observed with circularity and solidity (p < 0.001). Among the clinical features (patient age, sex, smoking habits, oncologic history, emphysema status, and PSN lobe location), only oncologic history (lung or other cancers) was strongly associated with nodule growth (p = 0.007).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…In their quantitative analysis, the authors defined growth as an increase by more than 11.3% (i.e., more than the coefficient of repeatability of intraobserver variability) of the linear mass density (LMD), a viable two-dimensional alternative to the mass. Moreover, to determine the nodule growth rate, the authors also calculated the LMD-DT by matching the baseline with the last available follow-up CT. Based on the results obtained in their study, Borghesi et al [29] found that both dimensional (area, perimeter, diameter, LMD) and shape features (circularity and solidity) were significantly related to nodule growth, and the strongest association was observed with circularity and solidity (p < 0.001). Among the clinical features (patient age, sex, smoking habits, oncologic history, emphysema status, and PSN lobe location), only oncologic history (lung or other cancers) was strongly associated with nodule growth (p = 0.007).…”
Section: Resultsmentioning
confidence: 92%
“…The other four original articles were published in 2019 [27][28][29][30]. Two articles, published by Shi et al [28] and Qi et al [30], focused exclusively on NSNs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations